Porcine fibrin sealant combined with autologous chondrocytes successfully promotes full‐thickness cartilage regeneration in a rabbit model. (4th June 2021) - Yang, Yu; Wang, Xin; Zha, Kangkang; Tian, Zhuang; Liu, Shuyun; Sui, Xiang; Wang, Zhigang; Zheng, Jilian; Wang, Jun; Tian, Xiaobin; Guo, Quanyi; Zhao, Jinmin
Abstract: Xenogeneic porcine fibrin sealant (PFS), derived from porcine blood, was used as a scaffold for cartilage tissue engineering. PFS has a porous microstructure, biocompatibility and degradation, and it provides a perfect extracellular matrix environment for the adhesion and proliferation of chondrocytes. Recently, PFS in combination with autologous chondrocytes (ACs) were used to study the microstructure of PFS scaffolds and promotion effect on the proliferation and migration of ACs. In this study, we investigated the effects of PFS in combination with ACs on the healing of cartilage defects in rabbits. A full‐thickness cartilage defect was made in the femoral trochlear in rabbits, subsequently, three surgical procedures were used to repair the defect, namely: the defect was treated with microfracture (MF group); the defect was filled with PFS alone (PFS group) or in combination with ACs (PFS + ACs group); the unrepaired cartilage defects served as the control group (CD group). Three and 6 months after the operation, the reparative effect was evaluated using medical imaging, gross scoring, pathological staining, biomechanical testing and biochemical examination. The PFS group showed a limited effect on defect repair, this result was significantly worse than the MF group. The best reparative effect was observed in the PFS + ACs group. These results hinted that PFS in combination with autologous chondrocytes has broad prospects for clinical applications in cartilage tissue engineering.